Physicians' continuing medical education activities and satisfaction with their ability to stay current in medical information and practice: A cross‐sectional study. Issue 2 (10th February 2023) - Jayas, Amy; Andriole, Dorothy A.; Grbic, Douglas; Hu, Xiaochu; Dill, Michael; Howley, Lisa D.
Abstract: Background and Aims: Little is known about physicians' approaches to continuing medical education (CME) for continuing professional development despite the rapid evolution of CME offerings. We sought to identify the extent to which demographic, career, and experiential CME‐activity variables were independently associated with physicians' satisfaction with their ability to stay current on medical information and practice. Methods: Using the 2019 Association of American Medical Colleges' National Sample Survey of Physicians data, we ran multivariable logistic regression models examining demographic, career, and experiential (participation in 11 CME activities in the past year) variables for their associations with physicians' satisfaction (satisfied vs. not satisfied/neutral) with their ability to stay current. Results: Of 5926 respondents, 90% (5341/5926) were satisfied with their ability to stay current. Significant (each two‐sided p < 0.05) predictors of respondents who were satisfied included (among others) a surgery specialty (vs. primary care; adjusted odds ratio [AOR] = 1.41, 95% confidence interval [CI] = 1.06–1.88), an academic affiliation (vs. none; AOR = 1.35, 95% CI = 1.10–1.66), and participation (vs. no participation) in each of professional meetings (AOR = 1.31, 95% CI = 1.07–1.60) and journal‐based CME (AOR = 1.29, 95% CI = 1.07–1.56). Respondents who self‐identified as a race/ethnicity underrepresented in medicine (vs. white; AOR = 0.68, 95% CI = 0.48–0.97) and were between ages 40 and 49 years (vs. 50–59; AOR = 0.74; 95% CI = 0.58–0.94) were less likely to be satisfied. Gender, board certification status, and medical degree type did not independently predict satisfaction (each p > 0.05). Conclusion: We observed independent associations between physicians' satisfaction with their ability to stay current in medical information and practice and each specialty, academic affiliation, race/ethnicity, age, and CME activity type (for 2 of 11 examined). Findings may be relevant to organizations and institutions designing and implementing CME activities in the current context of COVID‐19 pandemic‐related in‐person activity limitations and can inform targeted interventions addressing differences in the satisfaction we observed to better support physicians' CME.